Non- Distractive Testing of Reactive Powder Concrete (Journal of University of Babylon for Engineering Sciences, 2018)
This research focuses on estimating of three important properties of reactive powder concrete; the distractive, a non-distractive testing and statistical analysis suggest mathematical model. The ultrasonic pulse velocity test (NDT) method to study the properties of concrete. Fifty cubes with size (150mm), fifty cylinders with diameter (150mm), height (300 mm), and fifty prisms of dimensions (100*100*500) mm., Statistical analysis  was used to estimate the mechanical properties of reactive powder concrete (RPC), compressive strength, splitting tensile strength and flexural strength. Results showed that it is possible to estimate the mechanical properties using a mathematical model.